2019
DOI: 10.3390/ijms20102492
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PHRs and PCPs on Microalgal Growth, Metabolism and Microalgae-Based Bioremediation Processes: A Review

Abstract: In this review, the effect of pharmaceuticals (PHRs) and personal care products (PCPs) on microalgal growth and metabolism is reported. Concentrations of various PHRs and PCPs that cause inhibition and toxicity to growths of different microalgal strains are summarized and compared. The effect of PHRs and PCPs on microalgal metabolism (oxidative stress, enzyme activity, pigments, proteins, lipids, carbohydrates, toxins), as well as on the cellular morphology, is discussed. Literature data concerning the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 292 publications
(718 reference statements)
5
24
1
1
Order By: Relevance
“…This is quite understandable if we consider a species-specific differentiation in antibiotic tolerance, since our strains are much closely related to C. sorokiniana than C. vulgaris . Ciprofloxacin can also cause ≥30% inhibition in Chlorella pyrenoidosa at 100–150 mg l –1 (or μg ml –1 ); moreover, at concentrations comprised within 55–111 mg l –1 (or μg ml –1 ) it can inhibit the 50% growth of Chlamydomonas mexicana ( Miazek and Brozek-Pluska, 2019 ). Anyway, in these last examples, concentrations are much higher than those tested in our experiment (and in any case, higher than the ones commonly detected in environmental freshwater), and the investigated species are not related to our strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is quite understandable if we consider a species-specific differentiation in antibiotic tolerance, since our strains are much closely related to C. sorokiniana than C. vulgaris . Ciprofloxacin can also cause ≥30% inhibition in Chlorella pyrenoidosa at 100–150 mg l –1 (or μg ml –1 ); moreover, at concentrations comprised within 55–111 mg l –1 (or μg ml –1 ) it can inhibit the 50% growth of Chlamydomonas mexicana ( Miazek and Brozek-Pluska, 2019 ). Anyway, in these last examples, concentrations are much higher than those tested in our experiment (and in any case, higher than the ones commonly detected in environmental freshwater), and the investigated species are not related to our strains.…”
Section: Discussionmentioning
confidence: 99%
“…Benzylpenicillin (penicillin G) is an antibiotic widely used for the treatment of the common bacterial infections including pneumonia, strep throat, syphilis, necrotizing enterocolitis, diphtheria, gas gangrene, leptospirosis, cellulitis, and tetanus ( Stuart et al, 2009 ). It contains a 6-[(2-phenylacetyl)amino] moiety in its structure ( Miazek and Brozek-Pluska, 2019 ), and its inhibitory effect against Microcystis aeruginosa growth has been demonstrated at 0.006 mg l –1 ( Halling-Sorensen, 2000 ). This result is not in agreement with our observations, demonstrating that our strains, even if belonging to different genera/species, can tolerate much higher concentrations of this antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Organic microcontaminants in aquatic environments can cause toxic effects on microorganisms, such as microalgae [ 24 ]. Therefore, most researchers [ 25 , 26 , 27 ] have attempted to evaluate the individual effects of organic microcontaminants on microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been carried out to evaluate the toxicities of PhACs to microalgae (Miazek & Brozek‐Pluska, 2019). In general, the results suggested that PhACs at certain levels (ng/L or µg/L) did not exhibit acute toxicity to microalgae, but information concerning their chronic effects is still limited (Miazek & Brozek‐Pluska, 2019; W. Zhang et al, 2012). Most of the reported studies considered short exposure times, such as 24, 72, or 96 hr (Yang et al, 2008; Zounková et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been carried out to evaluate the toxicities of PhACs to microalgae (Miazek & Brozek-Pluska, 2019). In general, the results suggested that PhACs at certain levels (ng/L or µg/L) did not exhibit acute toxicity to microalgae, but information T A B L E 1 Structural formulae of the PhACs studied and some of their physicochemical characteristics concerning their chronic effects is still limited (Miazek & Brozek-Pluska, 2019;W. Zhang et al, 2012).…”
mentioning
confidence: 99%